2022
DOI: 10.1186/s12964-022-00881-9
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 regulates chondrocyte proliferation and extracellular matrix synthesis via circPhf21a-Vegfa axis in osteoarthritis

Abstract: Background The transforming growth factor-beta (TGF-β) signaling pathway is an important pathway associated with the pathogenesis of osteoarthritis (OA). This study was to investigate the involvement of circRNAs in the TGF-β signaling pathway. Methods Cell Counting Kit-8 (CCK-8) assay and 5-ethynyl-2′-deoxyuridine (EdU) assay were used to detect the proliferation of primary mouse chondrocytes (PMCs). RNA-sequencing together with bioinformatics anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…For example, circ_0000423 regulates cartilage ECM synthesis through the miRNA-27b-3p/MMP-13 axis 29 . TGF-β1 regulates chondrocyte proliferation and extracellular matrix synthesis in osteoarthritis through the circPhf21a-Vegfa axis 30 . circCDK14 ameliorated IL-1β-induced osteoarthritis chondrocyte injury through the miR-1183/KLF5 pathway 31 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, circ_0000423 regulates cartilage ECM synthesis through the miRNA-27b-3p/MMP-13 axis 29 . TGF-β1 regulates chondrocyte proliferation and extracellular matrix synthesis in osteoarthritis through the circPhf21a-Vegfa axis 30 . circCDK14 ameliorated IL-1β-induced osteoarthritis chondrocyte injury through the miR-1183/KLF5 pathway 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Kubosch et al has shown that the co-culture of chondrocytes with human synovial MSCs (SMSCs) leads to self-organization, chondrogenic differentiation of SMSC, and TGFβ secretion 43 . In addition, researchers demonstrated that TGFβ could stimulate chondrogenesis by provoking the expression of Sox9 and Col II, and TGFβ signaling could lead to further stimulation of chondrocyte proliferation and inhibition of chondrocyte hypertrophy 44 , 45 . These data justify our results about the increasing diameter of micromass by Co-ag-EV and MSC-ag-EV and their chondrogenic potential on MSC micromass culture, but more research is still required, especially about the existence of TGFβ in Cho-ag-EV.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of total protein from chondrocytes was performed using RIPA lysis buffer (Solarbio, China) supplemented with 1% PMSF protease inhibitor (Solarbio, China). Western blotting was performed following established protocols as described in our previous work 32 . Firstly, the protein concentrations were determined using the Enhanced Bicinchoninic Acid (BCA) protein assay kit (Beyotime, China).…”
Section: Methodsmentioning
confidence: 99%